Gangguan Kecemasan Berpisah Pada Anak Usia Dini dan Penanganan Dalam Perspektif Islam - Putri Ratih Puspitasari; Sopiah Sopiah; Eva Riza; Asep Irwansyah; Mansur Mansur (Peneliti.net, 2023)
This research is a literature study that discusses separation anxiety disorder in early childhood. The purpose of this study is to describe how the phenomenon of separation anxiety develops from infant, toodler and preeschool ages. Separation anxiety can be a mental disorder that must be handled properly by teachers and parents. This research uses library research. The collected research data is then analyzed using Description Analysis Content, with the stages of data reduction, data presentation and data verification. The results of this study indicate that separation anxiety disorder occurs when children have to separate from attached figures. Parents and teachers must be able to understand comprehensively the factors that cause children to experience separation anxiety disorder and provide treatment for separation anxiety disorder in children from an Islamic perspective through parental intervention activities according to the example of the Prophet Muhammad.